A TEACHER'S WRITTEN FEEDBACK ON STUDENTS' WRITING: A Descriptive Study at One Public Junior High School in Bandung - Sulistianingsih, Dwi Elis (2017)
This study examines the teacher's written feedback on students' writing (a descriptive study at one public junior high school in Bandung). The objective of this study is to find out the strategies of feedback employed by the teacher in giving written feedback on students' writing. Also, it intends to see the students' responses to teacher's written feedback on their writing. It employed a descriptive case study, involving an English teacher who taught thirty five students at one of public junior high school in Bandung. The data were gathered from classroom observation, students' document collection, questionnaire and interviews. The obtained data were mainly analyzed based on Ferris (2003), Ferris (2006) and Hedge (1998) explaining the theory of strategies in providing written feedback. The findings showed that the teacher's written feedback enhances students' writing in term of grammar and mechanics of writing, the enhancement was influenced by teacher's direct and indirect feedback. In direct feedback strategy, the students understand their mistakes and know what and how they have to do to revise their own mistakes. Meanwhile, in indirect feedback strategy, the teacher provided feedback by giving commentary and symbols on his students' writing. In indirect feedback, symbols were more frequently employed by the teacher on students' writing. Students also responded positively to the feedback provided by the teacher since feedback helped them to write better in the future. In conclusion, feedback from the teacher is an essential aspect for students in helping them make a better writing. However, for the sake of clarity and understanding, it is also important for teachers to pay attention on the forms of feedback given. Keywords: Written Feedback, Direct Feedback, Indirect Feedback, Writing Penelitian ini menguji masukan dari guru secara tertulis terhadap tulisan siswa (studi deskriptif di salah satu sekolah umum SMP di Bandung). Tujuan dari penelitian ini adalah untuk mengetahui strategi umpan balik yang digunakan oleh guru dalam memberikan umpan balik tertulis terhadap tulisan siswa. Selain itu, studi ini juga meneliti tentang respon siswa terhadap umpan balik tertulis yang diberikan guru mereka didalam tulisan mereka. Studi ini menggunakan studi kasus deskriptif, yang melibatkan seorang guru bahasa Inggris yang mengajar tiga puluh lima siswa di salah satu sekolah umum menengah pertama di Bandung. Pengumpulan data studi ini terdiri dari observasi kelas, tulisan siswa, kuesioner dan wawancara. Data yang diperoleh berdasarkan Ferris (2003), Ferris (2006) dan Hedge (1998) menjelaskan teori strategi dalam memberikan umpan balik tertulis. Hasil dari temuan ini menunjukkan bahwa umpan balik tertulis guru dapat meningkatkan tulisan siswa, terutama dalam hal tata bahasa dan mekanik penulisan, peningkatan itu dipengaruhi oleh umpan balik langsung dan tidak langsung dari guru. Dalam strategi umpan balik langsung, siswa memahami kesalahan mereka dan mengerti bagaimana cara memperbaiki kesalahan mereka sendiri didalam tulisan mereka. Sementara itu, dalam strategi umpan balik tidak langsung, guru memberikan umpan balik dengan memberikan komentar dan simbol pada tulisan siswa. Dalam umpan balik tidak langsung, guru lebih sering menggunakan simbol dalam memberikan umpan balik tidak langsung untuk mengidentifikasi kesalahan siswa. Siswa juga merespon positif terhadap umpan balik yang diberikan oleh guru karena umpan balik yang diberikan oleh guru dapat membantu mereka untuk memperbaiki tulisan mereka menjadi lebih baik di masa depan. Kesimpulannya, umpan balik dari guru merupakan aspek penting bagi siswa dalam membantu siswa dalam memperbaiki tulisan mereka mereka. Namun, demi kejelasan dan pemahaman, penting juga bagi guru untuk memperhatikan bentuk umpan balik yang diberikan terhadap tulisan siswa. Kata kunci: Umpan Balik Tertulis, Umpan Balik Langsung, Umpan Balik tidak langsung, Menulis